INFORMATION AND COMMUNICATION TECHNOLOGIES IN PHYSICAL EDUCATION AND SPORTS (GYMNASIUM, 2009)
ICT stands for the English: “Information and Communication Technologies”, and its Frenchequivalent is TIC, meaning: “Technologies de l’Information et de la Communication”.Thus explaining that in the Romanian language, the usage of both collocations is permitted,depending on the speaker, if he is either English-speaking or Francophone. In any case, both options areviable and stand for “Information and Communication Technologies”, about which a lot of dictionaries,including “Techencyclopedia” says “it is the umbrella term that covers the whole of the computertechnology”, generally referred to as IT (Information Technology).